Pengukuran Aktivitas Nitrat Reduktase (ANR) Pada Tanaman Poaceae Secara In vivo - Devi Bunga Pagalla; Magfirahtul Jannah (Universitas Medan Area, 2023)
Corn, rice, and sugarcane are included in the Poaceae family which have high economic value as staple foods. Nitrate reductase plays a role in reducing nitrate to ammonia. The nitrate reductase activity testing can help biotechnology studies, in this case, fertilizer production or organic waste treatment, because the nitrate reductase enzyme can be used to convert nitrate into more useful nitrogen compounds. The purpose of this study was to analyze the activity of nitrate reductase (ANR) from the leaves of the Poaceae family, namely corn, rice, and sugarcane. In vivo ANR measurements were carried out using the spectrophotometric method with two types of spectrophotometers, namely the Vis/UV Spectrophotometer, Genesys10UV, and Visible Spectrophotometer, with a wavelength of 540 nm. This study concludes that rice had the highest ANR of 0.1503 µmol/gram leaf weight/hour of incubation. The increase in nitrate reductase activity indicates that the energy for nitrate reduction also increases and provides a large capacity for synthesizing amino acids, proteins, or total N assimilation.